Indices of Serum Tonicity in Clinical Practice. (June 2015) - Rohrscheib, Mark; Rondon-Berrios, Helbert; Argyropoulos, Christos; Glew, Robert H.; Murata, Glen H.; Tzamaloukas, Antonios H.
<x xml:space="preserve">Abstract</x> Abstract: Although disturbances of serum tonicity (effective osmolality) may have dire consequences, only surrogate indices of tonicity are available in practice. This report identifies the appropriate index for expressing clinical states of dystonicity. Serum sodium concentration ([Na]S) and osmolality ([Osm]S) may be incongruent. When the tonicity state shown by [Osm]S is higher than [Na]S and the difference between the 2 indices is caused by an excess of solute that distributes in total body water, tonicity is described by [Na]S. When this difference results from a gain of solute with extracellular distribution like mannitol or a decrease in serum water content, causing a falsely low measurement of [Na]S, [Osm]S accurately reflects tonicity. Two indices of tonicity are applicable during hyperglycemia: the tonicity formula (2·[Na]S + [Glucose]S/18) and the corrected [Na]S ([Na]S corrected to a normal [Glucose]S using an empirically derived coefficient). Clinicians should understand the uses and limitations of the tonicity indices.